Unlearning: a key to develop organizational learning? - Elisa, Roblot (Conferência - Investigação e Intervenção em Recursos Humanos, 2019)
Organizational Learning was described as if organizations only needed to add knowledge to trigger learning whereas Learning Organizations (Senge, P-M., 1990) were characterized as a king of ideal to achieve through triple loop organizational learning (Argyris C. and Schön D., 1978).Both were criticized because they have sparsely been studied regarding Unlearning (Love et al., 2000; Wong and Cheung, 2008). Besides, works have focused on the result of Unlearning, taking for granted that discarding knowledge could automatically bring about useful new practices (Prahalad & Bettis, 1986, p. 498, Argote, 1999, p. 92). They have claimed it could be easily managed to bring about change through controlled learning, at individual and collective levels (Wittorski R., 2008, p. 28) and thus help an organizational learning strategy (Wong and al., 2012, p.95; Tidd et al., 2006). Their utilitarian perspective has prevented them from considering the process itself and more precisely how it happens at these levels, neither phenomena that could impede unlearning. Our communication will explore the process itself and the many factors that can make unlearning end in something else that learning. In addition it will provide HR managers with keys to foster staff learning, taking account of their past experience and through reflexivity.